A New High‐Order Adaptive Robust Control for Constraint Following of Mechanical Systems. Issue 5 (10th February 2017) - Wang, Xiuye; Zhao, Han; Sun, Qinqin; Chen, Ye‐Hwa
Abstract: A mechanical system is to follow a class of prescribed holonomic or nonholonomic constraints. The system contains time‐varying bounded uncertainty. However, the bound is unknown. The objective is to design a control which renders constraint following. A new high‐order adaptive robust control is proposed. The control guarantees uniform boundedness and uniform ultimate boundedness even in the presence of the uncertainty. Significant advantages of this new control are demonstrated both analytically and numerically. It is shown that the system performance, including the finite entering time, constraint‐following error, and control magnitude, can be improved by tuning the control order.